Plant-Derived Nano and Microvesicles for Human Health and Therapeutic Potential in Nanomedicine - Mariaevelina Alfieri; Antonietta Leone; Alfredo Ambrosone (MDPI AG, 2021)
Plants produce different types of nano and micro-sized vesicles. Observed for the first time in the 60s, plant nano and microvesicles (PDVs) and their biological role have been inexplicably under investigated for a long time. Proteomic and metabolomic approaches revealed that PDVs carry numerous proteins with antifungal and antimicrobial activity, as well as bioactive metabolites with high pharmaceutical interest. PDVs have also been shown to be also involved in the intercellular transfer of small non-coding RNAs such as microRNAs, suggesting fascinating mechanisms of long-distance gene regulation and horizontal transfer of regulatory RNAs and inter-kingdom communications. High loading capacity, intrinsic biological activities, biocompatibility, and easy permeabilization in cell compartments make plant-derived vesicles excellent natural or bioengineered nanotools for biomedical applications. Growing evidence indicates that PDVs may exert anti-inflammatory, anti-oxidant, and anticancer activities in different in vitro and in vivo models. In addition, clinical trials are currently in progress to test the effectiveness of plant EVs in reducing insulin resistance and in preventing side effects of chemotherapy treatments. In this review, we concisely introduce PDVs, discuss shortly their most important biological and physiological roles in plants and provide clues on the use and the bioengineering of plant nano and microvesicles to develop innovative therapeutic tools in nanomedicine, able to encompass the current drawbacks in the delivery systems in nutraceutical and pharmaceutical technology. Finally, we predict that the advent of intense research efforts on PDVs may disclose new frontiers in plant biotechnology applied to nanomedicine.